What Do Weather Disasters Cost? An Analysis of Weather Impacts in Tanzania - Msemo, Hellen E.; Taylor, Andrea L.; Birch, Cathryn E.; Dougill, Andrew J.; Hartley, Andrew; Woodhams, Beth J. (Frontiers in Climate, 2021)
WWeather-related disasters negatively impact livelihoods and socioeconomic activities and often lead to the loss of lives and homes. This study uses disaster data from the Disaster Management Department (DMD) in Tanzania to describe the spatial distribution of weather-related disasters, their socioeconomic impacts and highlight opportunities to improve production and uptake of weather and climate information by climate sensitive sectors. Between 2000 and 2019, severe weather accounted for approximately 69% of disasters in Tanzania. The Government spent over 20.5 million USD in response to these disasters, which destroyed over 35,700 houses and 1,000 critical infrastructures (roads, bridges, schools and hospitals), affected over 572,600 people, caused over 240 injuries and 450 deaths. To reduce these impacts, it is important to understand the decision-|making process in terms of what and how national guidelines create and enabling environment for integration of weather and climate information into disaster risk reduction strategies. For example, the National Transport Policy which is supposed to provide cross-sectorial guidelines on the use of weather and climate information addresses the use to marine industry but remains silent to other climate sensitive sectors and the public. Whilst weather warnings are available Tanzania continues to suffer from the impacts of weather-related disasters. There is a clear need to better understand the value of weather warning information at short timescales (1-5 days) and how this information can be better used in the individual decision-making processes of those receiving advisories and warnings. The review of policies to guide on cross- sectoral actions to foster the uptake of weather and climate services, decisions across climate sensitive sectors, both nationally and sub-national level is recommended.